OVERLAY THICKNESS PLANNING ANALYSIS FLEXIBLE PAVEMENT RUNWAY TORAJA AIRPORT SOUTH SULAWESI - Agustin, Wahyu Shesar; Triyono, Agus; Winiasri, Linda (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Toraja Airport is an airport located in Tana Toraja Regency, South Sulawesi Province. The airport has a runway with dimensions of 2000 m x 30 m and the most critical aircraft, the ATR 72-600. Currently, Toraja Airport has problems, namely Weathering and Raveling on the runway surface. Therefore, further handling is needed in the form of overlays to prevent bad things from happening in flight operations. This study aims to determine the needs and plan the thickness of the overlay on the runway of Toraja Airport. This study uses the FAARFIELD (Federal Aviation Administration Rigid and Flexible Iterative Elastic Layer Design) method. In this study, several stages were carried out. The stages include overlay planning with FAARFIELD and calculating the Draft Budget Cost for the Toraja Airport runway overlay work. The results of this study show that the overlay planning covers the entire runway area of 2000 m x 30 m. The overlay thickness requirement on the runway of Toraja Airport is 50.8 mm or equivalent to 5 cm. Based on the Cost Budget Plan that has been made, the cost is IDR 4,957,900,000.00 (four billion nine hundred and fifty-seven million nine hundred thousand rupiah).